OmpA and Rz/Rz1: A Research Perspective - Tessa Sjahriani; Eddy Bagus Wasito; Wiwiek Tyasningsih (Research Perspectives of Microbiology and Biotechnology Vol. 4, 2024)
This study aimed to analyze the amino acid of OmpA and Rz/Rz1 of lytic bacteriophage from Surabaya, Indonesia. Porines are a type of \(β\)-barrel proteins with diffuse channels and OmpA, which has a role in hydrophilic transport, is the most frequent porin in E. coli, it was also chosen as the potential receptor of the phage. Some bacteriophages pierce the bacterial cell wall with their "needles" by a mechanical mechanism, like a syringe, to facilitate their entry. Without endangering the cell’s ability to survive, bacteriophages employ the enzymes in their tails. On the other hand, the Rz/Rz1 protein frequently causes significant bacterial cell wall disintegration as part of the mechanism for the release of progeny virions from infected bacteria, which results in host cell lysis. This study employed a sample of 8 bacteriophages from the previous study. The OmpA analysis method was Mass Spectrometry. Analyzed Rz/Rz1 using PCR, DNA sequencing, Expasy Translation, and Expasy Protparam. The result obtained 10% to 29% sequence coverage of OmpA, carrying the ligand binding site. The Rz/Rz1 gene shares a high percentage of 97.04% to 98.89% identities with the Siphoviridae isolate ctTwQ4, partial genome, and Myoviridae isolate cthRA4, partial genome. The Mann Whitney statistical tests indicate the significant differences between Alanine, Aspartate, Glycine, Proline, Serine (p = 0.011), Asparagine, Cysteine (p = 0.009), Isoleucine (p = 0.043), Lysine (p = 0.034), Methionine (p = 0.001), Threonine (p = 0.018), and Tryptophane (p = 0.007) of OmpA and Rz/Rz1. The conclusion obtained from this study is OmpA acts as Phage 1, Phage 2, Phage 3, Phage 5, and Phage 6 receptor for its peptide composition comprising the ligand binding site, and Rz/Rz1 participate in host bacteria lysis. The Rz/Rz1 specialized machinery is triggered to break down the cell walls of bacteria in order to achieve this goal. This mixture may have the ability to lyse and eradicate bacterial strains, which could result in the creation of novel narrow- spectrum antibiotics.